1985
DOI: 10.1128/jvi.54.3.889-893.1985
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence analysis of endogenous murine leukemia virus-related proviral clones reveals primer-binding sites for glutamine tRNA

Abstract: Nucleotide sequences of the region that corresponds to the site of tRNA primer binding for a functional retrovirus were determined in five murine leukemia virus-related sequence clones from mouse chromosomal DNA, which contain a unique 170 to 200-base-pair additional internal segment in the long terminal repeats. The 3'-terminal 18-nucleotide sequence of a major glutamine tRNA isoacceptor was found to match well with the putative primer binding site: 18 of 18 in three clones, 17 of 18 in one clone, and 16 of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…A stretch of 18 bp, located immediately downstream of the 5' U5 region, was examined to determine PBSs for the putative MuERVs. The conserved PBS sequences for tRNA Proline (P) and tRNA Glutamine (Q) were used as references (Harada, Peters, and Dahlberg, 1979;Nikbakht et al, 1985).…”
Section: Pbs Analysismentioning
confidence: 99%
“…A stretch of 18 bp, located immediately downstream of the 5' U5 region, was examined to determine PBSs for the putative MuERVs. The conserved PBS sequences for tRNA Proline (P) and tRNA Glutamine (Q) were used as references (Harada, Peters, and Dahlberg, 1979;Nikbakht et al, 1985).…”
Section: Pbs Analysismentioning
confidence: 99%
“…Furthermore, analysis of pol mutants of Moloney MLV demonstrated that the presence in MLV virions of tRNA Pro correctly annealed to the PBS is independent of products of the pol gene (13). Additional indications for a less stringent use of tRNA primers in MLV come from sequencing of MLV-related viruses endogenous to the murine genome carrying PBSs that match tRNA Gln (10,31).…”
mentioning
confidence: 99%
“…The remaining endogenous viruses, present at between 12 and 30 copies (44), have not yet been systematically studied, although a number of isolated proviruses have been examined in varying detail (28,30,52). These viruses differ from the inducible ecotropic and xenotropic viruses in a number of respects, including long terminal repeat (LTR) size (29, 45), tRNA primer-binding site (42), and the sequences of their eait' genes (28,32). Studies of cloned proviruses have not revealed major differences among the nonecotropic proviruses; however, analyses of genomic DNA have provided suggestive evidence for the presence of two classes of nonecotropic, nonxenotropic viruses differing slightly in the distribution of restriction endonuclease cleavage sites (15,55).…”
mentioning
confidence: 99%